Sustainability of Fossil Fuels - Strizhak, Pavel A. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The energy and fuel industries represent an extensive field for the development and implementation of solutions aimed at improving the technological, environmental, and economic performance of technological cycles. In recent years, the issues of ecology and energy security have become especially important. Energy is firmly connected with all spheres of human economic life but, unfortunately, it also has an extremely negative (often fatal) effect on the environment and public health. Depletion of energy resources, the complexity of their extraction, and transportation are also problems of a global scale. Therefore, it is especially important nowadays to try to take care of nature and think about the resources that are necessary for future generations. For scientific teams in different countries, the development of sustainable and safe technologies for the use of fuels in the energy sector will be a challenge in the coming decades